2014
DOI: 10.1016/j.joca.2014.02.602
|View full text |Cite
|
Sign up to set email alerts
|

Chondroprotective activity of acti-joint®, a combination of chondroitin sulfate, glucosamine and a natural ingredient rich in hyaluronic acid

Abstract: and, in addition to its powerful antioxidant activity, it may exert modulatory effects on different signalling pathways. Methods: The immortalized human cell line C-28/I2 and primary cultures of human chondrocytes (prepared from fragments of articular cartilage obtained from adult OA patients undergoing knee arthroplasty) were treated with HT, 30 minutes before exposition to hydrogen peroxide to induce oxidative stress and samples were collected at different times. We tested cell viability through reading on M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Research is still underway for the ideal procedure. Recently, disease-modifying agents have been emphasized [4,7,8]. Several studies have been conducted on HA and have been reported in many studies that have modified OA.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Research is still underway for the ideal procedure. Recently, disease-modifying agents have been emphasized [4,7,8]. Several studies have been conducted on HA and have been reported in many studies that have modified OA.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, HA is routinely used in the treatment of joint OA. There are very few studies in the literature comparing the effects of intra-articular administration of GS and HA [4,8,18].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations